A Technical Note: on Microspheres - Rupali, Sable P.; Anuja, Gawai G.; Vrunda, Rajput J.; Subodh, Urkunde A.; C Atram, Dr. Sandeep (Asian Journal of Pharmaceutical Research and Development, 2024)
Microspheres have become a center of research. Microspheres are an excellent way to deliver drugs to specific sites and control their effects. They are characterized by free-flowing spheres composed of biodegradable or non-biodegradable proteins or synthetic polymers, with an ideal particle size of 1-1000 microns. Microspheres encapsulate active pharmaceutical ingredients (APIs) in a polymer matrix that protects the API from environmental degradation. Pharmacokinetic limitations can be overcome by modifying the formulation to release the drug slowly during prolonged action. The purpose of this review is to list the different types of microspheres, their different preparations, limitations, advantages and disadvantages, characterization, applications, and recent developments in microspheres and various compatibility studies.